Analisis miskonsepsi materi ipa pada tema panas dan perpindahannya - Alfianita Nur Fadhilah; Idam Ragil Widianto Atmojo; Dwi Yuniasih Saputri (Universitas Sebelas Maret, 2022)
This study aims to analyze the misconceptions of science material theme VI heat and its transfer in fifth grade elementary school students. This type of research is a qualitative approach. Data collection techniques in the form of four-level diagnostic tests and interviews. The sampling technique used was purposive sampling, namely all fifth grade students of SDN 1 Krasak Boyolali. The results showed that students of SDN 1 Krasak Boyolali had misconceptions on all subconcepts of the science material theme VI of heat and its displacement. The conclusion of this study is that the misconceptions that occur in students are 29.33% in the low category. The lowest misconception with a percentage of 23.32% is in the subconcepts of conductors and insulators. The highest misconception lies in the sub-concept of the difference in temperature and heat with a percentage of 36.65%. Factors that cause misconceptions in students come from wrong preconceptions, low interest in learning and improper reasoning.